Tabletop belt sander machine - Zahid, Ahmad Daniel Haiqal; Md Isa, Kamariah; Manssor, Nur Aini Sabrin (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Carpentry activities often necessitate the use of a belt sander machine to expedite the shaping and finishing of products. However, conventional belt sander machines’ high cost proves impractical for smaller-scale projects, creating a barrier to accessibility. To address this issue, the project's objective is to develop a tabletop belt sander machine, tailored for finishing on a smaller scale. The innovation involves integrating a disc sander machine with the belt sander, resulting in a versatile single tool that combines two essential processes. The machine's frame, constructed from mild steel, houses a dual shaft 12 V motor, enabling it to function as both a belt and disc sander. Moreover, equipped with a speed controller, users can conveniently adjust the belt and disc rotation speeds to meet specific requirements. The tabletop belt sander machine is affordable for users with smaller carpentry projects, providing a practical alternative to costly and oversized equipment. The compact design ensures efficient space utilization while maintaining a reasonable operating speed suitable for diverse tasks. In conclusion, the potential impact of this innovation extends to enhancing accessibility and productivity in the carpentry industry, offering a cost-efficient and practical solution for shaping and finishing wood and materials on a smaller scale. The compact, versatile, and budget friendly nature of this machine opens new opportunities for diverse woodworking projects.